GAMBARAN KONSEP DIRI DAN KOMUNIKASI INTERPERSONAL PADA DOKTER MUDA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Sunarti "; Elda Nazriati; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTSelf-concept is self image of individual about himself or herself that was formed through the experiences gained from interaction with environment. Interpersonal communication is a communication that happen between two or more people by direct contact through face to face or communication media in the form of a conversation to get a response directly. Clerkship must have self-concept and good interpersonal communication. The aim of this study was to find out the self-concept and interpersonal communication of clerkships in Medical Faculty of Riau University. Desain of this study used descriptive with cross-sectional method. Samples of this study were 155 clerkships who selected by minimal sample which will be divided in every station with proportional random sampling. Collecting data used self-concept questionnaire developed by the researcher based on theory of Fitts and interpersonal communication questionnaire based on theory of Devito. The result indicate that self-concept of clerkships in Medical Faculty of Riau University were positive (53,5%). The dimensions of self-concept in order from the highest to the lowest are judging self, moral-ethical self, family self, personal self, physical self, identity self, social self and behavior self. Whereas the majority of interpersonal communication were moderate category (69,7%) and there were not significantly different in characteristics of interpersonal communication effectiveness.Keywords: self-concept, interpersonal communication, clerkship